Seasonal abundance and distribution of dragonflies in upper Siran valley of District Mansehra Pakistan - Mehmood,S. A. (2021)
Abstract Present study was conducted to study seasonal abundance and distribution of dragonflies in upper Siran valley district Mansehra Pakistan. To collect data, eleven localities were visited for three consecutive years (2016-2018). Results come up with a sum of 300 specimens identified under three families, eight genera and twenty species. Highest seasonal abundance recorded during summer and spring were 80.67% and 13.33% respectively while minimum 6.00% was recorded during early autumn. Dominant species observed were, Orthetrum chrysis (14.00%), followed by O. gluacum (12.00%), Palpoleura sexmaculata sexmaculata (11.33%) and O. cancellatum cancellatum (8.00%). However the highest population of dragonflies was found in Munda Gucha with a percentage of 11.33 followed by Jabbar (11.00%) and Sachan (9.67%). The lowest populations were recorded in Suham (6.00%), Dadar (7.67%) and Jabori (7.67%). The surveyed valley showed diverse Anisopterous fauna and thus further extensive surveys are recommended that can come up with more important species from the area.